1989
DOI: 10.1159/000293604
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Echocardiography in Hypertensive Pregnancies

Abstract: Echocardiographic hemodynamic and left ventricular parameters were determined in 14 normotensive and 18 hypertensive women during the last trimester of pregnancy. The hypertensive patients had significantly higher mean values of total peripheral resistance (p < 0.001), maximum velocity of posterior wall motion (p < 0.05), mean velocity of circumferential fiber shortening (p < 0.01) and percent fiber shortening of left ventricular diameter (p < 0.05). The mean values for heart rate, stroke volume, cardiac outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…Discrepancies in the findings related to systolic function, it was described as increased or remained unchanged. In our study, the EF and shortening fraction increased in PIH patients that in accordance with most of other investigations 5,12 . In Blanco's study, no significant difference was found in shortening fraction between the normal pregnant women and women with PIH 13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Discrepancies in the findings related to systolic function, it was described as increased or remained unchanged. In our study, the EF and shortening fraction increased in PIH patients that in accordance with most of other investigations 5,12 . In Blanco's study, no significant difference was found in shortening fraction between the normal pregnant women and women with PIH 13 .…”
Section: Discussionsupporting
confidence: 92%
“…The echocardiographic results showed that the end‐diastolic IVS was thickened significantly in PIH compared with that in NP, and the left ventrticular posterior wall was also thickened, although with no significant difference, which demonstrated the asymmetrical hypertrophy in PIH in our study and corresponded with the study conducted by Blanco 4 . While Degani 5 found that no significant differences existed between patients with PIH and women with normal pregnancy in both the thickness of left ventricular posterior wall and the IVS. The discrepancies of these results might be due to the different severity and trimesters of the patients with PIH as they were studied.…”
Section: Discussionsupporting
confidence: 86%
“…We are not aware of earlier data on atrial dimensions in pre‐eclampsia. Earlier ultrasonographic studies have focused on ventricular function and have provided evidence of increased cardiac contractility 6 . The novel findings in the present study were increased left atrial and aortic dimensions and the frequent occurrence of pericardial effusion in pre‐eclamptic women.…”
Section: Discussionsupporting
confidence: 59%
“…This condition strains the heart, although increased blood pressure and vasospasm may be the underlying factors in this rather than an increase in blood volume. Ultrasonographic studies of the maternal heart have shown an increase in maternal cardiac contractility related to the elevated peripheral vascular resistance observed in pre‐eclampsia 6 . Haemodynamic adjustment in the early puerperium in pre‐eclamptic pregnancies has been insufficiently studied, however, and we are not aware of any data on the puerperal changes in heart dimensions or ANP levels in this condition.…”
Section: Introductionmentioning
confidence: 88%
“…19 It may be useful as an adjunct to other haemodynamic monitoring in an elective delivery for a parturient with cardiac compromise. 20,21 The use of this technology in parturients has been extensively explored in a recent review article by Dennis. 22 The advantage of TOE over TTE is that of clearer images due to a reduction in signal attenuation by the chest wall, especially of the aorta, valvular structures, and coronary arteries.…”
Section: Transthoracic and Transoesophageal Echocardiographymentioning
confidence: 99%